2017
DOI: 10.1103/physreva.95.052327
|View full text |Cite
|
Sign up to set email alerts
|

Nonholonomic tomography. I. The Born rule as a connection between experiments

Abstract: In the context of quantum tomography, we recently introduced a quantity called a partial determinant [1]. PDs (partial determinants) are explicit functions of the collected data which are sensitive to the presence of state-preparation-and-measurment (SPAM) correlated errors. As such, PDs bypass the need to estimate state-preparation or measurement parameters individually. In the present work, we suggest a theoretical perspective for the PD. We show that the PD is a holonomy and that the notions of state, measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…One last form of quantum tomography is state-preparation-and-measurement (SPAM) tomography [21][22][23][24][25]. SPAM tomography attempts to estimate both the state and measurement parameters in a self-consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…One last form of quantum tomography is state-preparation-and-measurement (SPAM) tomography [21][22][23][24][25]. SPAM tomography attempts to estimate both the state and measurement parameters in a self-consistent manner.…”
Section: Introductionmentioning
confidence: 99%
“…2 (a)-(b). We find that ( ) 2 Tr 0.866 ρ = ; this is a measure of the purity of the state. We then fit our measured ρ These parameters indicate that our source produces a state that is well described by Eq.…”
Section: No Background Illuminationmentioning
confidence: 84%
“…It is called the partial determinant because it is mathematically similar to the determinant, but it is not a scalar quantity-it is a matrix of smaller size than E . It can be shown that the measured data are internally consistent as described above, and free of correlated SPAM errors, if and only if ( ) 1 E D = , where 1 is the 3x3 identity matrix [1][2][3][4]. No knowledge of the state ρ or the detector operators is necessary to make this determination.…”
Section: A Loop Spam Tomographymentioning
confidence: 89%
See 1 more Smart Citation
“…. Moreover, this example illustrates that noise can be artificially reassigned to different objects, as the state in equation (2) is closer to pure than the one in equation (9). Note that the range of gauge transformations is constrained by ò 2 and so cannot significantly change the effective temperature for systems with high quality readout.…”
Section: Assigning Errors To Operationsmentioning
confidence: 93%